Digital Transformation Readiness of Electrical Equipment Manufacturing Enterprises in Hanoi - Dan, Nguyen Thi Thanh; Chuong, Nguyen Quang (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
The study of digital transformation that leads to the implementation of the digital economy is a matter of special concern for businesses around the world. This study systematizes the theoretical basis of digital transformation in manufacturing enterprises and on that basis analyzes the current status and readiness for digital transformation of electrical equipment manufacturers in Hanoi. The analysis results show that electrical equipment manufacturing enterprises in Hanoi are at the beginning of digital transformation. Overall, companies show the highest levels of digital readiness in forward and backward linkages. The study also provides recommendations for businesses in the process of implementing digital transformation and recommendations on the state's macro policies in creating favorable conditions for businesses to successfully implement digital transformation in the future.